Delayed onset muscle soreness (DOMS) management: present state of the art - Contro, V.; Pieretta Mancuso, E.; Proia, P. (Trends in Sport Sciences, 2016)
This paper reviews existing theories explaining the delayed onset muscle soreness (DOMS) phenomenon. The authors describe the main symptoms of DOMS and their relation to different kinds of training strategies, and discuss the most popular muscle pain reduction interventions such as stretching, diet, dietary supplements, nonsteroidal anti-inflammatory drugs (NSAIDs), cryotherapy and cold water immersion, concurrent training, and the repeated bout effect.